Transparency and Its Impact on Achieving The Organizational Reputation. - سعيد هديل كاظم; عباس زياد علي (Journal of Economics and Administrative Sciences, 2017)
This research test the relationship and the effect of an explanatory variable transparency in the organizational reputation responder variable by senior management in the departments of the Ministry of Housing and Construction centrally funded, As well as come out among other recommendations contribute to the achievement of organizational reputation of the organizations surveyed. Given the importance of the research topic for the public sector and the community and the environment in which they operate researcher designed questionnaire containing (30) items, and collected data from (92) respondents, representing the research community (eight establishments) exclusively and comprehensively, relying descriptive analytical method, Accounting for the research community to (general managers, aides general managers, heads of departments) as the most specialized and their office gives them the ability to achieve organizational reputation, and in the light of that has been collecting and analyzing data and test hypotheses using software (SPSS V.21, EXCEL 2010) with the adoption of methods descriptive statistics which is b (percentages, the arithmetic mean, variance, relative importance, simple PEARSON correlation coefficient and simple linear regression), The researcher reached to an association and effect correlation high transparency in the organizational reputation with their application clearly in the surveyed organizations, while providing better service to beneficiaries and the development of a climate encourages creativity, but that in spite of the work to the principle of openness in the announcement of tenders and auctions for everyone, but it continues to suffer the prevalence of a culture of secrecy and monopoly of information, the main recommendations were given to high-quality staff bonuses fit their output and strengthen decision-making supported by an efficient system of communication systems .